PERBANDINGAN KANDUNGAN FLAVONOID EKSTRAK ETANOL DAUN DAN BUAH CEPOKA (SOLANUM TORVUM SWARTZ) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Fatdhilah Febyari; Bida Cincin Kirana; Angga Rahabistara Sumadji (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2023)
Cepoka (Solanum torvum Swartz.) included in the herbaceous plants it can be cultivated as a traditional medicinal material. The parts most used as traditional medicine are the leaves and fruits. Cepoka leaves contain alkaloid compounds, flavonoids, quinone, polyphenols, saponins, steroids, monoterpenoids. While in the fruit chemical content is alkaloid compounds, saponins, anthraquinone, tannins, flavonoids and glycosides. The purpose of this study is compared flavonoid levels in leaves and fruit cepoka. The extraction method uses maceration method with 96% ethanol solvent. Flavonoid level was measured with Spectrophotometer UV-Vis and quercetin standard.. The results of this study show that the content of flavonoids in the leaves cepoka amounted to 14.6346% W / W while the fruit contains cepoka flavonoids 0.9768% W / W.